Research on the design concept of three-dimensional ecological building - Sun Yutong; Sun Haibo; Dong Yu (E3S Web of Conferences, 2024)
This chapter highlights the significance of three-dimensional ecological architecture as a crucial direction for the development of green architecture in China. The design concept is centered around four main principles: green, energy-saving, user-friendly, and ecological circulation. This case analysis demonstrates the effectiveness of incorporating ecological elements and sustainable design strategies into building structures, resulting in reduced energy consumption, improved indoor environmental quality, and enhanced biodiversity. The chapter explores the development trends and insights derived from one case study, providing valuable references for China future advancement of green architecture.